Social image in public goods provision with real effort - Emel Filiz-Ozbay; Erkut Y. Ozbay (TÜSİAD-Koç University Economic Research Forum, 2010)
We study public goods game where the contribution efforts are observable. When the players are observed, they contribute more and free-riding diminishes significantly. On the other hand, presence of an audience does not affect the performance of players if there is no strategic aspect of the game, i.e. when they play private goods game. The findings are in line with the predictions of the social image theory where a player's contribution is also a signal to an audience regarding how much she cares about contributing to the public goods.
Keywords: 330; public goods; effort; experiment; social image; Öffentliches Gut; Soziales Verhalten; Test